Impaired awareness of self and others: exploring insight into illness and theory of mind in opioid dependent patients undergoing opioid maintenance treatment. - Eidenmüller, Katharina (2023)
Insight into illness is relevant to treatment motivation and clinical outcomes in psychiatric disorders. Various studies have found insight to be impaired in patients with substance use disorders. Surprisingly, this includes patients in opioid maintenance therapy, who by the nature of their treatment are regularly confronted with their opioid dependence and thereby might be expected to have gained a certain level of insight into their substance use disorder. However, despite the clinical relevance of insight, there is a lack of research on mechanisms underlying impaired insight in substance use disorders. Literature on insight in mental illness reveals three explanatory approaches: The deficit approach suspects deficits in executive functioning at the core of impaired insight. The nondeficit approach frames impaired insight as the result of motivational processes connected to avoiding negative consequences of stigma. The cognitive neuropsychological perspective understands impaired insight as a consequence of poor theory of mind. Similarly to insight, theory of mind has been linked to clinically relevant factors and shown to be impaired in opioid dependent patients, but very little is known about influences on theory of mind impairments in this population. The aim of this dissertation was to gain a better understanding of insight into illness and theory of mind in opioid dependent patients and influencing factors on both. In the first study, significant deficits in theory of mind were found in patients in opioid maintenance treatment. These deficits correlated with physical abuse and neglect in childhood and components of executive functioning, but not with variables related to substance abuse. This suggests that theory of mind impairments could be a risk factor predating substance abuse. In study two, insight into illness was shown to be impaired in the majority of the sample of opioid dependent patients. Insight did not correlate with substance use related or sociodemographic variables. Neither executive functioning, nor theory of mind were associated with insight, hence the deficit approach and the cognitive neuropsychological perspective could not be confirmed for opioid dependent patients. Insight into illness was associated with stigma resistance and correlated inversely with self-stigma, which can be interpreted as supporting the nondeficit approach for insight in opioid dependence. In conclusion, there is a need for further research in order to better understand, firstly, the relationship between theory of mind, executive functions and childhood trauma; secondly, the relationship between insight into illness and self-stigma; and thirdly, the potential role of impaired theory of mind as a risk factor for substance abuse. Moreover, theory of mind, insight into illness and self-stigma are promising targets for clinical interventions for opioid dependent patients.
Keywords: Hochschulschrift